Linkage analysis of tourism‐related sectors in China: An assessment based on network analysis technique - Zha, Jianping; Shao, Yuhong; Li, Zhiyong (The international journal of tourism research, 2019)
Based on China's Input–Output Tables of 2002, 2007, and 2012, this paper employs a network analysis technique to evaluate the roles, positions, and evolution of tourism‐related sectors in industrial networks. The results revealed that China's tourism industrial network has loose density. The tourism‐related sectors have limited backward linkage effects and play limited intermediary roles in resource flows with regard to the rest of the economy, and the linkage strengths vary by sector. The sectors that occupy the same roles and positions as the tourism‐related sectors are concentrated in tertiary sectors. The service‐economy features of tourism‐related sectors are increasingly significant.